WOMEN EMANCIPATION THROUGH LAW AND JUDICIAL DECISIONS: AN INSIGHT. - Jan, Aneeda (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human beings are born free and so does a woman believe. The constitution of India guarantees a right to equality to all citizens regardless, of their gender and prohibits discrimination on the grounds based on sex, caste, etc. It has made a special provision for women under Article 15 Clause 3 of the constitution so that their rights and interests are protected. The rationale behind this is to uphold their freedom and status as guaranteed. Recently the Supreme Court made the daughters equal co-heirs to the sons. The court interpreted section 6 of the Hindu Succession Act,1955 to include daughters as coparceners by birth and ended the uncertainty over the correct interpretation of the section. Similarly, the Supreme Court ruled that the restriction of women to enter Sabarimala Temple is gender discrimination. The Apex Court by 4:1 held that prohibiting the entry of women into the temple based on biological differences violates the right to equality under Article 14 and the right to freedom of religion conferred by Article 25 of the constitution. This research will attempt to analyse the role of the judiciary in attempting to remove the age-old discrimination against women.